The influence of arc's voltage on the weld dimensions - Palić, Vlastimir (Journal of Production Engineering, 1989)
In this paper, a one-factorial experiment was conducted to determine the influence of changing the arc's voltage on the dimensions of the weld's cross-section. Domestic welding materials were used, with an electrode wire of 5 mm diameter.